Penyelamat yang Memberikan Kesempatan Berbuah Mendatangkan Kehidupan Menurut Lukas 13:6-9 - Rosmini Setiawati Zai Ros; Hendi Wijaya (STT INTI Bandung, 2022)
This article is the result of research from the gospel of Luke 13:6-9. In this study, the author finds a spiritual meaning contained in it, which then raises the theme, namely about an opportunity to grow and bear fruit that comes from a helper bringing life according to the gospel of Luke 13:6-9. The method used is the method of parable exegesis using parable analysis. In the discussion, the fig tree that does not bear fruit and only has leaves is a picture of every human life who sometimes lives like believers because of the spiritual activities they show in public. However, in reality it is just an image. They are not people who really believe because they do not produce actions as the fruit of true faith. God as the owner of the vineyard, was finally angry to find humans who behaved like that. So that in the end God brought His punishment to humans. Jesus Christ, who was the gardener, finally intervened to defend the fruitless fig tree by asking God for mercy. For that, everyone responds to the mercy of Christ in his life by turning to God and being fruitful in Christ.